2014
DOI: 10.1038/ejcn.2013.273
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the iodine status and the correlation between iodine nutrition and thyroid function during pregnancy in an iodine sufficient area

Abstract: In our cohort of pregnant women the iodine intakes were sufficient, and no correlation between urinary iodine concentration and thyroid function tests was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 26 publications
4
9
2
2
Order By: Relevance
“…In our study, among PW in the countries with sufficient or more-than-adequate iodine intake, no statistically significant correlation was found between Tg and UIC or press.endocrine.org/journal/jcemTSH or TT4, in agreement with previous studies of PW (8,(36)(37)(38)(39). This might result by the iodine-deficient thyroid upregulating thyroid hormone synthesis and maintaining euthyroidism through mechanisms independent of TSH (40,41).…”
Section: Discussionsupporting
confidence: 81%
“…In our study, among PW in the countries with sufficient or more-than-adequate iodine intake, no statistically significant correlation was found between Tg and UIC or press.endocrine.org/journal/jcemTSH or TT4, in agreement with previous studies of PW (8,(36)(37)(38)(39). This might result by the iodine-deficient thyroid upregulating thyroid hormone synthesis and maintaining euthyroidism through mechanisms independent of TSH (40,41).…”
Section: Discussionsupporting
confidence: 81%
“…26 In this study, although T3 was higher in both deficient and mildly deficient women compared with sufficient women, there were no differences in T3/T4 ratio between the groups. Several studies report no associations between maternal UIC and thyroid function, 21 , 27 , 28 and in a study comparable to the present, 29 no associations between UIC and repeated measures of THs were found. However, that study population were classified as iodine sufficient (median UIC 160 μg/l in second trimester), hence, the influence on thyroid function by severity and timing of iodine deficiency vary between study populations and can explain discrepancies between study results.…”
Section: Discussionsupporting
confidence: 69%
“…For example, Kim et al found that the 24-h urinary iodine excretion correlated more strongly with the iodine:creatinine ratio rather than with the simple UIC [36] . Other authors discourage the use of the iodine:creatinine ratio because of its higher variability [2,35] . Our results are consistent with the latter observation and fail to give evidence of a substantial advantage in normalization to urine creatinine levels.…”
Section: Discussionmentioning
confidence: 98%
“…Iodine is the major component of thyroid hormones and neurodevelopment of the fetus and breast-fed infants are crucially affected by maternal iodine intake [1,2] . The key indicator of population iodine nutrition recommended by the World Health Organization (WHO) is represented by the median concentration of UIC measured by a 24-h collection (gold standard) or by more practical single spot samples [2 -5] : a median UIC of at least 100 μ g/L represents an adequate iodine nutrition in a population and UIC equal to 300 μ g/L was set as upper normal limit [3] .…”
Section: Introductionmentioning
confidence: 99%